Clinical and laboratory predictors for acquiring COVID-19 infections in patients on maintenance hemodialysis in 5th wave of epidemic in Myanmar - Pyar, Khin Phyu; Hla, Sai Aik; Lwin, Kyaw Thu Yein; Aung, Zar Ni Htet; Myat, Kaung; Maung, Lay Maung; Hein, Ye Min; Aung, Lynn Htet; Thant, Myo Min; Maung, Myo Maung; Zaw, Moe Htun; Mg, Ye Htook; et al. (Jour Med Resh and Health Sci, 2022)
Background: Patients on maintenance hemodialysis (MHD) are at high risk of contracting SARS-CoV-2 and developing severe COVID-19 infection because they have low innate immunity as well as poor antibody response to COVID-19 vaccine. This study aimed to assess the clinical and laboratory predictors for 5th wave of COVID-19 infections in patients on maintenance hemodialysis. Methods: A hospital based, case control study was conducted in July 2022 to November 2022 among patients on MHD who had confirmed COVID-19 infection by nasopharyngeal swab PCR. Data were collected by using standardized forms and analysis was done. Results: A total of 22 patients out of 61 patients on maintenance hemodialysis ( MHD) developed COVID-19 infection in same public hemodialysis (HD) center in Yangon. The comparison of clinical and laboratory parameters (age, BMI, vaccination history, type of vaccine, duration from last vaccination , smoking status, vaccination time, comorbid status, duration of hemodialysis, hemoglobin level, serum albumin level and anti-Spike antibody level) was made between infected group and non-infected group. Patients in both groups had 4 doses of vaccine: Covaxin, Sinovax, Sinopharm and Covishield. Baseline clinical characteristics were not significantly different between infected cases and non-infected cases; mean age was 49.77 ± 11.58 years vs 51.92 ± 13.6 years; BMI was 19.75 ± 3.00 kg/m2 vs 20.03 ± 2.76 kg/m2 ; duration from last vaccination was 37.64 ± 2.22 days vs 38.77 ± 3.62 days; number of current smokers was 4 vs 8 ; and vaccination time in the morning was 14 vs 29 patients. The proportion of patients with past COVID-19 infection was the same; 63.6% (14/22) in infected group and 66.7 % (26/39) in non-infected group. Hemoglobin level was lower in infected groups (8.26 ± 2.07 gm% vs 8.33 ± 2.02 gm%); and serum albumin level was lower in infected group (42.47 ± 4.82 gm/dl vs 43.17 ± 4.10 gm/dl) too. The race, religion, comorbid status (diabetic nephropathy, coronary heart disease) and the duration of hemodialysis was not different between 2 groups. The proportion of patients with cerebrovascular accident was higher in infected group. Median (IQR) anti-Spike antibody level of infected cases was 4732 (5206) U/mL and it was 3195 (4883) U/mL in non-infected cases; it was not different significantly. Conclusions: The baseline characteristics like age, race, religion, BMI, comorbid status (diabetic nephropathy, coronary heart disease), smoking status, duration of hemodialysis, past COVID-19 infection, anti-Spike antibody level, vaccination time and duration from last vaccination were non-predictors for 5th wave of COVID-19 infection among patients on MHD who had 4 doses of COVID-19 vaccine. The likely predictors were cerebrovascular accident, low hemoglobin and low serum albumin.